Mediation of Organizational Citizenship Behavior Between Organizational Justice and Public Medical Practitioners’ Turnover Intention: Personal Norm of Reciprocity as Moderator - Ahmad Rafeein bin Mohamad (Universiti Sains Islam Malaysia, 2025)
Matric: 4201097 (FKP) Restricted until May 2028